Determination of movement and behavior of Atlantic salmon smolts at the Vernon Hydroelectric Station - RMC Environmental Services Inc (ScholarWorks@UMass Amherst, 1990)
Behavior of emigrating Atlantic salmon smolts was evaluated at New England Power Company's (NEP) Vernon Hydroelectric Station. The objectives of this study were to determine smolt travel time from Bellows Falls to Vernon Dam, approach routes, residency periods, and exit routes at the station. A total of 122 smolts was radio tagged and released below Bellows Falls Station in four groups of 30, 30, 30, and 32. Four smolts were excluded from data analysis. A total of 35.6% of the remaining 118 smolts was detected at Vernon Dam within 13 h 39 min to 142 h 24 min (Mean = 44 hr 25 min) after release. Of these, 88.1% approached the station from the eastern side of the river, 9.5 approached on the west side, and 2.4% approached from mid-river. Residency times at the dam were short and ranged from <1 min to 5 days (Mean = 8 hr 9 min) and decreased for the last two groups released. This was most likely due to higher river flows availing multiple passage routes (open tainter gates). Passage routes at Vernon Station were determined for 40 smolts. Of these, 42.9% utilized open tainter gates, 21.4% passed through the sluice gate, and the remaining 30.9% passed through generating turbines. Passage routes for two other smolts detected at the station were not determined.